Mobile Based Application For Vaccination Searching and Scheduling - Yanto Setiawan; Fadhil Shofian; Fauzi Nur Noviansyah; Maulana Aji Satrio (Syntax Corporation, 2022)
The goal of this thesis is to produce a mobile application which works on both Android and iOS devices to help people to find information about vaccination places and do the registration process in the chosen place. This application is expected to create vaccination places which follows currently applied health protocol by limiting the number of people who are going to take a vaccine. In addition, users can also view vaccination certificates as proof that they have been vaccinated through the application. The application development process uses waterfall method. Evaluation is done by distributing questionnaires and drawing conclusions based on the results of the questionnaire